POLIMORFISME GEN GROWTH HORMONE (GH) TERHADAP SIFAT PRODUKSI SUSU SAPI FRIESIAN HOLSTEIN DI BALAI PEMBIBITAN TERNAK UNGGUL HIJAUAN PAKAN TERNAK (BPTU-HPT) BATURRADEN - , DIAN KURNIAWATI; , Tety Hartatik, S.Pt., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conduct to know polymorphism GH gene and allele frequency of FH, and associated of effect of genotype and breed with milk yield, fat and protein content. The research was conduct at BPTU-HPT Baturraden, and Animal Breeding Laboratory UGM. The research was use 62 FH at BPTUHPT Baturraden, consist of 19 FH imported from New Zealand and 43 FH imported from Australia. Blood sampel for DNA molecular analysis was conducted by DNA isolation with SDS-PK modification method, DNA amplification with Polymerase Chain Reaction (PCR) method use the primer pair, GH-Forward: 5â-GCTGCTCC TGAGGGCCCTTC-3â and GH-reverse: 5â- CATGACCCTCAGGTACGTCTC CG-3â, and digesti with Restriction Fragment Length Polymorphism (RLFP) method. Association between effect of genotype and breed with milk production can know by Randomized Complete Block Design (RCBD) analysis. Identification of GH gene polymorphism was conducted by digested the DNA fragment of 211 bp by Alu I enzyme. The result indicated that Sequencing alignment prove that the sequence of FH was found Single Nucleotide Polymorphism (SNP), where there is substitution cytocin (C) to guanine (G) at position 2141 (GenBank No.M57764) which resulted in changes in the amino acid sequence leucine to valine. Frequencies of L and V allele in FH imported from New Zealand 0.92 and 0.08 respectively with genotype LL 0.84 and LV 0.16. Frequencies of L and V allele in FH imported from Australia 0.90 and 0.10 respectively with genotype LL 0.79 and LV 0.21. In this study indicated that effect of genotype with milk yield, fat and protein content have not significant, but effect of breed with fat and protein milk content have significant. The conclusion this research showed that was found polymorphism in FH cows at BBPTU-HPT Baturraden. Associated between genotype with milk yield, fat and protein content was not found, but FH with LV genotype have positive effect for milk yield. Associated between breed with fat and protein content was found in FH cows at BPTU-HPT Baturraden. FH imported from Australia have higher than FH imported from New Zealand on fat and protein content Keywords: Polymorphism, Growth hormone gene, Milk production, Friesian Holstein